Palpebral schwannoma as an uncommon differential diagnosis in solid eyelid lesions - Gascón, Noemí Porras; Andrade, Cristian Notario; Flores, Jimena Celeste Treviño; Martínez, Oscar Ulises Rosales; González, Iván Yahir Paternina; Trejo, Brittani; González, Dulce Paola Gómez; Guzmán, Diana Guadalupe González (International Surgery Journal, 2025)
Schwannoma (neurilemmoma) is a rare benign tumor that originates from Schwann cells of peripheral nerves, accounting for approximately 0.1 to 0.7% of eyelid tumors. The occurrence of schwannoma in the eyelid is extremely rare, with very few cases reported in the literature to date. These tumors are typically solitary, asymptomatic, and slow-growing, which can make early diagnosis challenging. Clinically, they present as solid eyelid masses without skin involvement and can be mistaken for other conditions such as inclusion cysts, recurrent chalazia, or other types of tumors. A definitive diagnosis is obtained through histopathological and immunohistochemical studies. The treatment of choice is complete surgical excision, which generally has a favorable prognosis with a low recurrence rate. This case highlights the importance of always considering schwannomas in the differential diagnosis of any solid eyelid lesion.